The Influence of the Board of Commissioners and Audit Committee on Financial Performance with the as A Moderating Variables - Retno Wulandari (Journal of Research in Business, Economics, and Education, 2020)
This study has a purpose, namely to test and analyze the existence of a board of commissioners and audit committee on Banking Financial Performance in 2016-2019 with firm size as a moderating variable. The sampling technique was purposive judgment sampling and obtained 28 companies as the research sample. The data analysis technique applied is multiple regression analysis, classical assumption test and path test. The results of the analysis explain that the Independent Board of Commissioners partially has a negative impact on financial performance, the audit committee affects financial performance, and for firm size partially affects financial performance negatively. Regarding the results of the path test, it is found that firm size strengthens the relationship of the board of commissioners to financial performance. Finally, weakens the relationship between audit committees on financial performance.